2022
DOI: 10.3390/vaccines10111894
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Aging-Associated Poor Influenza Vaccine Responses with CpG 1018 Adjuvant

Abstract: Aging is associated with diminished immune system function, which renders old people vulnerable to influenza infection and also less responsive to influenza vaccination. This study explored whether the CpG 1018 adjuvant was effective in enhancing influenza vaccine efficacy in aged mice equivalent to human beings in their late 50s to early 60s. Using the influenza pandemic 2009 H1N1 (pdm09) vaccine as a model, we found that the CpG 1018 adjuvant could significantly enhance the pdm09 vaccine-induced serum antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recent studies (Kang et al and Strohmeier et al) have reported the potential of using CpG 1018 as an effective adjuvant to enhance the efficacy of recombinant HA and NA vaccines [ 46 , 47 ]. However, the immunostimulatory effect of CpG adjuvant alone on influenza vaccines remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (Kang et al and Strohmeier et al) have reported the potential of using CpG 1018 as an effective adjuvant to enhance the efficacy of recombinant HA and NA vaccines [ 46 , 47 ]. However, the immunostimulatory effect of CpG adjuvant alone on influenza vaccines remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a clinical study revealed that 1 mg of CpG 7909 failed to improve humoral responses induced by a trivalent split influenza vaccine [ 29 ]. Kang et al reported the immune response induced by 0.5 μg of recombinant HA and 40 μg of CpG 1018, but this did not meet the common licensing criteria (HI titre of ≥ 40), and only a 40% survival rate was observed after adjuvanting with CpG 1018 [ 46 ]. On the other hand, Strohmeier et al showed that at least 3 μg of recombinant NA antigen was required when adjuvanted with CpG alone to induce robust protection against virus challenge in a mouse model [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small volume of blood (~50 µL) was collected for measurement of serum antibody titer following procedures described in our previous reports [24,25]. In brief, 96-well plates were coated with 100 µg/mL OVA followed by blocking and incubation with 4-fold serial diluted serum samples.…”
Section: Serum Antibody Titermentioning
confidence: 99%
“…CpG-ODN, a clinically approved Toll-like receptor 9 (TLR-9) agonist for cancer immunotherapy, was adopted as a positive control in this study due to its high capacity to facilitate the elicitation of cytotoxic T lymphocyte (CTL) immunological responses according to previous studies. 45 , 46 , 47 These mice received corresponding subcutaneous (s.c.) injections once a week three times, and the injection doses of OVA, Mn 2+ and CpG were 5.6 mg/kg, 1.5 mg/kg, and 1 mg/kg, respectively. ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%